A CHKA–PML autophagy checkpoint enables tumors to evade glutamine starvation - Ruijie Wang; Leixi Cao; Xianwei He; Rick Francis Thorne; Qichen Wu; Caoyuan Ding; Jinjing Zhang; Mengfan Li; Zeyuan Shi; Xinyi Dong; Jing Li; Hongxiang Li; et al. (Proceedings of the National Academy of Sciences, 2026)
Glutamine metabolism is essential for tumor cell proliferation and biosynthesis. However, solid tumors often face chronic glutamine deprivation, and the underlying adaptive mechanisms remain incompletely understood. Here, we show that glutamine scarcity upregulates choline kinase alpha (CHKA), whose monomerization enhances its noncanonical protein kinase activity. CHKA phosphorylates promyelocytic leukemia (PML) at tyrosine 339, promoting its cytoplasmic localization. Notably, this reflects a compartment-specific switch in PML activity: while nuclear PML facilitates protein degradation through Small Ubiquitin-like Modifier (SUMO)-ubiquitin cascades, cytoplasmic PML acts oppositely to block degradation. Specifically, cytoplasmic PML then induces SUMOylation of WD Repeat Domain Phosphoinositide-Interacting Protein 2 (WIPI2) at lysines 281 and 283, thereby blocking HUWE1-mediated ubiquitination and proteasomal degradation. Stabilized WIPI2 increases autophagic flux, supporting tumor cell survival under metabolic stress. This study identifies a critical CHKA–PML–WIPI2 axis mediating adaptation to glutamine deprivation, providing insight into metabolic plasticity and a potential therapeutic target for glutamine-dependent cancers.